PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN CITRA TERHADAP TINGKAT KEPUASAN PASIEN RAWAT INAP (Students' Journal of Economic and Management, 2013)
This research is a study that tested the effect of price perceptions, quality of service and image. The purpose of this study were: 1) examine the effect of price perception on the level of patient satisfaction in hospitals Dr. Soewondo Kendal. 2) test the effect of Service Quality on the level of satisfaction of hospitalized patients. 3) test the effect of imagery on the level satisfaction hospital inpatients Dr. Soewondo Kendal. Factor Price Perception, Image Quality and service are some of the factors that influence patient satisfaction. The study was conducted on patients hospitalized at the Hospital Dr. Soewondo Kendal. Respondents are being sampled in this study were 95 respondents with sampling methods using purposive sampling. The results showed that, The first hypothesis accepted, meaning that the more positive perception of the price received by patients will increase patient satisfaction. The second hypothesis is accepted it means the better the quality of service will further enhance the satisfaction. The third hypothesis is accepted it means that the better the image will further enhance the satisfaction. So it can be concluded to build the necessary patient satisfaction among perceptions of price, quality of service and a good image.Key words: Price Perception, Service Quality, Image and Patient Satisfaction